INCREASING THE CAPACITY OF CADRE FOR CONTROLLING HIGH BLOOD PRESSURE (HYPERTENSION) IN THE COMMUNITY IN THE WORKING AREA OF CIBADAK HEALTH CENTER RANGKASBITUNG LEBAK DISTRICT - Rokayah, Yayah; Husnida, Nintinjri; Yuningsih, Nani; Iswanti, Tutik; Widjanarko, Bangun (POLTEKKES KEMENKES BANTEN, 2023)
57 million (63%) mortality occurs in the world, and 36 million (43%) morbidity is caused by non-communicable diseases. WHO in 2010 reported that 60% of the causes of death for all ages in the world were PTM and 4% died before the age of 70 years. Community service in the regional partnership program contributed to the Cibadak Rangkasbitung Community Health Center program with the Lebak District Health Office, PTM patient care with hypertension control. Efforts by the Health Office, Cibadak Health Center to educate the community on prevention, control through POSBINDU, training of cadres in the village on hypertension control. not yet optimal and evenly reach the community. The solution is to increase the understanding of cadres in the village of the Cibadak Community Health Center who have not had training in controlling high blood pressure (hypertension). The method of carrying out the Pre test, providing information inviting health service resource persons to increase the cadre's understanding of the concept of hypertension, prevention efforts, early detection. Lecturers train the skills of cadres to measure blood pressure with digital blood pressure. The next meeting was Post test, Monev cadres conducted education, examined 5 patients with high risk of hypertension. There was an increase in the average score of community knowledge about hypertension from 64.3% to 88.3% from 64.3%, there was an increase in the skills of cadres to measure blood pressure with digital blood pressure from 5 people to 12 people. As a continuation of activities, there needs to be community participation, good cooperation between health cadres and village supervisors, program holders